Buying and Selling Online from the Perspective of Hadith Science: (Jual Beli Online dalam Perspektif Hadis) - D Dadah; Sergie Ahmad Ramadhan; Faiz Zulfan Akbar; Wiksan Zujalis (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2024)
The aim of this research is to elucidate how the law of online trading is viewed from the perspective of Hadith. Many Hadiths discuss trading, and several of them are utilized to understand the legal aspects of online trading. In this digital era, the use of online trading methods is widespread. However, we must pay closer attention when using these methods. This research employs a qualitative method with a descriptive approach. Regarding the discussion that follows, we have collected data from books and journals, utilizing a library research method. Online trading also presents several issues, and Hadiths are used to provide solutions to these online trading problems